Bartlett Bros. packtrain hauling freight, Front St., Dawson, Yukon Territory, approximately 1898. - Hegg, Eric A., 1867-1948 (1898)
Caption on image: "Bartlett Bros. packtrain, Front Street Dawson". Klondike Gold Rush.